1999
DOI: 10.1007/s005990050062
|View full text |Cite
|
Sign up to set email alerts
|

Biliary bile acid composition in gastric cancer

Abstract: Bile reflux into the stomach has been considered carcinogenic. Secondary bile acids, and in particular deoxycholic acid, have been shown to act experimentally as co-carcinogens in the colon and are increased in patients with colorectal adenocarcinoma. No information is available with respect to biliary bile acid composition in patients with gastric cancer. We studied biliary bile acid composition in 11 patients with gastric cancer and 23 healthy controls. Bile acids were measured using high-performance liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…(19) On the other hand, no differences were found in secondary bile acid composition, including deoxycholic acid, between stomach cancer patients and a control group. (20) Even in our own study, no differences in the incidence of reflux or in its concentration were seen among the peptic ulcer disease group, gastritis group, and normal group. We therefore carried out our study of reflux bile acids regardless of the disease.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…(19) On the other hand, no differences were found in secondary bile acid composition, including deoxycholic acid, between stomach cancer patients and a control group. (20) Even in our own study, no differences in the incidence of reflux or in its concentration were seen among the peptic ulcer disease group, gastritis group, and normal group. We therefore carried out our study of reflux bile acids regardless of the disease.…”
Section: Discussioncontrasting
confidence: 62%
“…Based on the fact that many differentiated stomach cancers develop in gastric mucosa that exhibit intestinal metaplasia, Matsukura et al (20) reported that intestinal metaplasia in the gastric mucosa is a precancerous condition. In a study by Uemura et al (30) there was a high rate of development of stomach cancer in subjects with H. pylori infection, especially in patients with severe atrophic gastritis and severe intestinal metaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Bile reflux is often observed after cholecystectomy; a cohort study therefore examined cholecystectomy as a risk factor for gastric cancer [55], but their finding showed that cholecystectomy did not seem to be associated with an increased risk of gastric cancer. Fracchia et al [56] studied biliary bile acid composition in gastric cancer patients and healthy controls, and found that gastric cancer was not associated with increased levels of the more toxic secondary bile acids, especially DCA. Of particular interest, we [57] experienced two patients with double choledochus with ectopic drainage into the stomach associated with early gastric carcinoma.…”
Section: Mucosal Injury and Cell Proliferation Induced By Bile Juicementioning
confidence: 99%
“… 49 Bile acid is toxic to the gastric mucosa and is also considered a risk factor for the development of gastric cancer. 50 Primary DGR can occur due to antroduodenal motility disorder. Secondary DGR generally follows surgical alteration of gastroduodenal anatomy (pyloroplasty, distal gastric resection with Billroth I or II reconstruction) or cholecystectomy.…”
Section: Bile Acid Metabolism In Altered Conditionsmentioning
confidence: 99%